Bilancio POP Comune di Spilamberto2024 - 2025 (European journal of volunteering and community-based projects, 2026)
The POP Report 2024–2025 of the Municipality of Spilamberto represents a model of public reporting aimed at enhancing administrative transparency, civic participation, and the evaluation of public policies at the local level. Its main objective is to make information regarding the management of public resources accessible to citizens by integrating quantitative analysis tools and sustainability indicators to support more informed and data-driven administrative decision-making.The preparation of the report is the result of a scientific collaboration with the Department of Economics, Management and Quantitative Methods of the University of Milan, with the contribution of the Department of Management of the University of Turin. This collaboration ensures a rigorous methodological approach to the analysis of financial and socio-economic data related to the local context, avoiding self-referential interpretations and promoting a comparative assessment of local public policies.From a methodological perspective, the document adopts an integrated approach that combines economic and financial indicators, demographic data, and sustainability indicators linked to the 17 Sustainable Development Goals (SDGs) of the United Nations 2030 Agenda. For the first time, these indicators are adapted to the municipal level, enabling local policies to be connected to global sustainable development challenges and allowing the impact of administrative decisions to be monitored over time.The analysis of the territorial context highlights a municipality of approximately 13,000 inhabitants, characterized by a balanced demographic structure, an average age in line with the national figure, and a significant share of the population in working age. Socio-economic indicators show relatively high average income levels and an estimated employment rate between 72% and 75%, suggesting a dynamic local economic system supported by small and medium-sized enterprises.The document also examines the organizational structure of the municipality and the system of multi-level governance, highlighting the role of the Unione Terre di Castelli in the joint management of numerous public services, particularly in the fields of welfare, education, and security. A significant share of municipal expenditure is allocated to this institutional cooperation, reflecting an administrative model based on economies of scale and territorial integration of services.From a financial perspective, the consolidated financial statements show an overall solid financial position, with net equity accounting for more than half of total assets and a relatively low level of indebtedness. The annual financial result records a small deficit, below 1% of total revenues, mainly attributable to the performance of publicly owned companies rather than to weaknesses in the municipality’s direct management.Finally, the analysis of public expenditure highlights a concentration of resources in institutional services, social policies, and education. At the same time, the indicator of current expenditure per capita (approximately €650 per resident) is significantly lower than the national average for municipalities of similar size, suggesting a relatively high level of efficiency in the management of public resources.Overall, the POP Report can be considered an innovative instrument of public accountability that integrates economic analysis, sustainability, and institutional communication in order to strengthen the relationship between public administration and citizens and to promote a public management approach focused on transparency and the measurement of results.